Energy efficiency in the food retail sector: Barriers, drivers, and acceptable policies - Christopher Dixon-O'Mara; Lisa Ryan (University College Dublin, UCD School of Economics, 2017)
The objective of this research is to empirically examine the drivers and barriers to energy efficiency measures in an important energy-using sector, namely the food retail sector, and support more effective energy efficiency policies for this sector. Although food retailers consume a significant amount of energy due to the refrigeration, air conditioning and specialised lighting needs of stores, there has been little research in this sector on the barriers and drivers for implementing energy efficiency measures. A survey of small food retailers was carried out to understand the barriers and drivers to greater uptake of energy efficiency measures and to examine the acceptability of different energy efficiency policy options for food retailers. In addition, external stakeholders were consulted in order to validate and contextualise the results of the survey. We find there is a complementary relationship between energy efficiency barriers and drivers for food retailers that is remarkably coherent. We identify policies, such as subsidies and support for ESCOs, that both exploit the complementarities between barriers and drivers and are acceptable to food retailers also. This methodology should help identify and design more effective policies to deliver energy efficiency improvements in the food retail sector.
Keywords: 330